2018
DOI: 10.1159/000485029
|View full text |Cite
|
Sign up to set email alerts
|

Methadone Dose Adjustments, Plasma R-Methadone Levels and Therapeutic Outcome of Heroin Users: A Randomized Clinical Trial

Abstract: Aims: We aimed to improve the retention in treatment and therapeutic outcome of methadone maintenance treatment (MMT) patients by adjusting the oral methadone dose in order to reach a “target” plasma R-methadone level (80–250 ng/mL). Methods: A multicenter randomized controlled trial was organized. Results: The intention-to-treat statistical analysis showed that repeated dose adjustments performed in order to obtain therapeutic plasma R-methadone levels did not improve retention in treatment of heroin-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…The upper limit remained at 250 ng/mL, but in our population, a very limited number of patients reached such levels (Fig. 3a in Mannaioni et al [1]). Furthermore, we confirmed that plasma concentrations above 200 ng/mL were reached in patients with an oral methadone dose intake of as low as 60 or as high as 200 mg/day (see the above-mentioned Fig.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…The upper limit remained at 250 ng/mL, but in our population, a very limited number of patients reached such levels (Fig. 3a in Mannaioni et al [1]). Furthermore, we confirmed that plasma concentrations above 200 ng/mL were reached in patients with an oral methadone dose intake of as low as 60 or as high as 200 mg/day (see the above-mentioned Fig.…”
mentioning
confidence: 54%
“…The target therapeutic plasma R-methadone concentration for the treatment of severe heroin users in the methadone maintenance program (MMT) described in Mannaioni et al [1] was set at 80–250 ng/mL. The comment letter of de Bernardis suggests that by further increasing plasma R-methadone concentrations, a better therapeutic outcome could possibly be obtained.…”
mentioning
confidence: 99%
“…More recently, Meini et al [3], also acknowledged by Mannaioni et al [1], confirmed Eap’s results, showing in their sample of methadone-treated patients the presence of a R-methadone threshold of 200 ng/mL for absence of heroin use, and 250 ng/mL for absence of craving. According to Meini’s published data on graph, more than 40% of the heroin-using patients in his sample had trough R-methadone levels falling between 80 and 250 ng/mL.…”
mentioning
confidence: 62%
“…Mannaioni et al [1], in their recent ­randomised clinical trial on methadone dosing adjusted according to serum ­R-methadone levels, chose a target window of 80–250 ng/mL R-methadone based on results by Eap et al [2]. …”
mentioning
confidence: 99%
See 1 more Smart Citation